Dampak Game Online pada Hasil Belajar Siswa Kelas VI di SDM PUU UPPO - Ritti, Oktavianus; Lende, Petrus; Making, Samuel Rex M. (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the impact of online gaming on the learning outcomes of sixth-grade students at SDM Puu Uppo. The background of this study is based on the phenomenon of increasing intensity of online gaming among elementary school students, which is suspected to affect their concentration, motivation, and academic achievement. This study uses a qualitative approach with structured interviews as the main instrument, supplemented by documentation of students' daily test results. The research subjects are 20 sixth-grade students who were selected purposively to obtain a more in-depth picture of online gaming habits and their impact on learning. Research data was collected through interview guidelines that focused on the frequency of gaming, duration, and its impact on learning activities at home and at school. In addition, learning outcome data was obtained through students' daily test scores in several core subjects. The results showed that the majority of students who played online games intensively tended to experience a decline in their daily test scores. This was due to reduced study time, decreased concentration, and increased fatigue as a result of excessive playing time. Thus, it can be concluded that online games have a negative impact on the learning outcomes of sixth-grade students at SDM Puu Uppo, requiring parental guidance and wise control of online game use.